PENGARUH HARGA, LOKASI DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN DI RUMAH MAKAN BATU LAMBUIK KECAMATAN TANJUNG RAYA, KABUPATEN AGAM - Siti Nurul Aisyah; M. Imamuddin; Miswardi; Rusydi Fauzan (STKIP Subang, 2026)
The evolution of the culinary sector compels entrepreneurs to discern the elements that shape customer contentment to remain competitive. Batu Lambuik Restaurant in Tanjung Raya, Agam Regency, exhibits fluctuating visitor patterns, ostensibly influenced by price uncertainty, limited facilities, and inconsistency in product quality. This study employed a quantitative approach, engaging a cohort of patrons whose perceptions were collected via questionnaires and subsequently analyzed to evaluate validity, consistency, and inter-variable relationships through regression techniques and hypothesis testing. The findings reveal that price and location exert negligible impact on customer satisfaction, whereas product quality emerges as the principal determinant significantly enhancing contentment. Collectively, when considered in unison, the three variables manifest a tangible effect on satisfaction, though a portion of variation remains attributable to factors beyond the study’s scope. These insights underscore the critical importance of maintaining product quality consistency as a central strategy for elevating customer experience and satisfaction amidst the competitive culinary landscape.